An evaluation of resilience engineering to improve safety management performance using a social network analysis approach: Narrative review. - Habibi, Ehsanollah; Barakat, Samira; Saber, Elham (Work, 2025)
Background: Resilience is a system performance feature and integration in a management framework. The aim of resilience engineering (RE) is to improve the capacity to mitigate variations in system performance when faced with changes, disruptions, and uncertainties. Social network analysis (SNA) enables the examination of intricate human systems by visualizing and describing relationships among individuals, groups, and entities. Objective: This paper is aimed at evaluating RE to improve safety management performance using an SNA approach. Methods: In the present study, the databases ISI Web of Science, Scopus, PubMed Central, Science Direct, and Google Scholar were used. The keywords for the searches included 'resilience engineering', 'resilience', 'safety management', and 'social network analysis'. Results: SNA, which is frequently employed to examine relationships and structures within networks, offers valuable tools for analyzing and enhancing the resilience of interconnected systems. SNA is a quantitative approach rooted in graph theory and mathematical symbols. The process of SNA entails conducting a survey to gather data from participants, refining the collected data, and utilizing software such as Gephi to map social networks. Conclusions: Assessing the RE of organizations through SNA can provide a better understanding of how individuals and groups interact, and how determining the nature of these interactions can impact safety management performance. Because appropriate communication among employees, as well as appropriate and desirable communication between managers and employees, and vice versa, can play a significant role in improving safety management performance. Appropriate and desirable communications by creating a strong structure led to an increase in the organization's ability to respond to safety issues, effective improvement, and active participation in accident prevention, ultimately playing a very important role in enhancing organizational resilience in safety management performance.